Empowerment of Family in Early Detection of Total Growth at Puskesmas Karangrejo Metro - Islamiyati Islamiyati; Sadiman Sadiman; Yoga Triwijayanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The target number of children in early detection of child development and development in the working area of ??Puskesmas Karangrejo is 1,037 children, with details of 133 infants from 0 - 11 months and 904 children aged 12 - 72 months. Of these, the coverage for early detection until February 2020 is still low, namely at 6.7%. The purpose of the Community Service is to empower families in conducting early detection of toddler growth and development in the Karangrejo Health Center area. The method of activity is health education and empowerment of “active participation” of mothers toddler in stimulating and detecting the growth and development of their children. The result of mentoring was that there was progress in the developmental ability of 1 child who had not been able to walk at the age of 19 months, showing an increase in walking ability after 2 weeks of assistance. There was an increase in the knowledge of mothers / families about growth and development by 12.68 points. There was an increase in the frequency of implementing stimulation for child growth and development by mothers of under-five from 88.2% of mothers who had stimulated to 98.6% after mentoring. Continuity of family empowerment is needed regarding early detection of growth and development and not only involving mothers / families but also involving cadres.